Christians, Jews and Muslims in the Same Society: The Fall of Convivencia in Medieval Spain - Highfield, John R. L. (Studies in church history, 1978)
On 1 March 1492 the Jews were expelled from Spain. Ten years later the Moorish inhabitants of Castile were offered the alternative of conversion or emigration. The fate of the Moors in the kingdoms of the Crown of Aragon was deferred until the reign of the emperor Charles V. But though he kept the inquisition out of Aragon for forty years, he did not succeed in reconciling his Morisco subjects with their Christian brothers. Philip II failed much more notably. For his policy stimulated the great Morisco revolt of 1568-70. Thereafter they were scattered round the kingdom in a forced diaspora. In 1582 their expulsion was proposed in the council of state. Finally in 1609-10 the government of Philip III, chastened by the twelve years truce in the Netherlands, set about the expulsion of all the three hundred thousand or so Moriscos who remained.